Regional Identity of Rugova Region in Kosovo - Arsim Ejupi; Shkumbin Lushaj; Edon Shemsedini (Dela)
This article explores the complexity of regional identity in the context of the Rugova region of Kosovo, examining how historical, cultural, geographical and social factors shape people’s feelings and connections to their place of origin. Through a mixed-method the research explores the formation and evolution of regional identity over time. Findings reveal a strong sense of belonging to the Rugova community, transcending geographical boundaries and generational shifts. The analysis proves also the significance of cultural heritage, traditions, and geographical features in fostering regional identity, while also highlighting concerns about the impact of modernization and globalization on the preservation of traditions. Ultimately, the study elucidates the complex interplay between individual experiences, societal changes, and external influences in shaping regional identity dynamics, offering insights into the multifaceted nature of identity construction and preservation in the Rugova region.